Fluid-structure interaction of flexible collectors affects particle capture efficiency at ecologically relevant collector Reynolds numbers - Sewak, Kyle; Hassan, Marwan; Ackerman, Josef D. (Frontiers in Mechanical Engineering, 2024)
Introduction: The capture of suspended particles, which is an important process in many aquatic and terrestrial ecosystems, has been modeled using stationary rigid collectors and, more recently those that move in response to flow-induced vibrations. These models do not, however, account for collector flexibility, despite the fact that many biological collectors, especially aquatic collectors, exhibit flexibility.Methods: This study examined the effect of collector flexibility (indicated by the Young’s Modulus, E; range = 10–3–102 GPa) on particle capture efficiency (η; flux of captured particles: flux of particles) at different collector Reynolds numbers (Rec where the collector diameter [dc] is the length scale; range = 30–508) in a recirculating flow chamber.Results: Patterns in η were generally similar for flexible and rigid collectors until moderate Rec (∼374) when higher η were observed on the most flexible collectors. This threshold corresponded to periods of vortex induced motions in which the oscillation frequency of the collector transverse to the flow direction was >4 Hz and the maximum amplitude of the oscillation relative to dc was >60% in the transverse and >100% in the longitudinal direction.Discussion: Given the range in E examined in this study, it is likely that particle capture on flexible natural collectors has been underestimated using the standard model of a rigid stationary or oscillating collector. The role of collector flexibility should be considered in models and studies of particle capture in natural systems.